Teacher-Student Style Mismatch: Implications for English Language Learning and Classroom Dynamics - Andi Asrifan; Luís Miguel Oliveira de Barros Cardoso; K.J. Vargheese (English Department - University of Sultan Ageng Tirtayasa, 2025)
Comprehending discrepancies between instructor and student learning styles is crucial for enhancing English language acquisition and classroom interactions. This study specifically sought to (1) ascertain the degree of discrepancies between teachers’ instructional preferences and students’ learning styles, (2) investigate the impact of these discrepancies on student engagement, motivation, and classroom interaction, and (3) analyze the adaptive strategies utilized by both educators and learners. A convergent mixed-methods methodology was utilized, integrating surveys (VARK and Grasha inventory), classroom observations, and interviews with ten educators and one hundred students. The findings indicated a notable discrepancy: 70% of educators supported auditory-based education, whereas merely 30% of students preferred this approach, resulting in diminished engagement, frustration, and disengagement among visual and kinesthetic learners. Nonetheless, certain students formulated adaptive tactics, including the creation of visual aids and collaboration with others. These findings underscore the necessity for multimodal instructional strategies and specialized teacher training to cultivate inclusive educational settings.